Masticatory Changes as a Result of Oral Disorders in Smokers - Rech, Rafaela Soares; Santos, Karoline Weber dos; Maahs, Marcia Angelica Peters; Vidor, Deisi Cristina Gollo Marques (International Archives of Otorhinolaryngology, 2014)
Introduction For chewing to occur properly, it is necessary that all oral structures are present and of normal standard.Objectives The aim of this study is to verify the presence of oral changes in smokers and the impact of the changes on masticatory function compared with individuals who never smoked.Methods Forty-eight subjects were evaluated, split into two study groups (24 subjects each) of current tobacco users and individuals who have never smoked. The variables halitosis, presence of lesions suggestive of caries and periodontal problems, number of teeth, classification of malocclusions according to angle, standard grinding food, chewing pattern, and speed of chewing were evaluated.Results There was no statistically significant difference in tooth loss between the groups, but the smokers had more losses manifesting malocclusion. Most smokers had halitosis and lesions suggestive of caries and periodontal problems; the halitosis was associated with the latter variable. Masticatory speed was also reduced significantly in these individuals compared with the control group when associated with occlusal alterations, in addition to grinding food with the tongue. No difference was observed regarding the chewing pattern. The presence of halitosis and periodontal problems were more common in those who smoke more than 20 years.Conclusion There is an association between smoking and dental changes, which cause increased masticatory changes.
Keywords: mastication; malocclusion; halitosis; smoking; stomatognathic system